2020
DOI: 10.1037/amp0000692
|View full text |Cite
|
Sign up to set email alerts
|

Negative cognitive and psychological correlates of mandatory quarantine during the initial COVID-19 outbreak in China.

Abstract: This study suggests that mandatorily quarantined individuals are more likely to have mental distress and negative cognitions related to COVID-19 than their nonquarantined counterparts. Attention should be paid to the heightened perceived discrimination as it was associated with both mandatory quarantine status and negative mental health status. The findings demonstrate the need to develop interventions to meet the psychological needs of people in quarantine during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
166
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(197 citation statements)
references
References 54 publications
22
166
2
7
Order By: Relevance
“…Besides the differences in the mean levels, these appraisals were associated with the outcomes differentially. Among the three appraisals, perceived severity was the risk factor that most widely associated with emotional and behavioural reactions, which is consistent with prior studies [22][23][24][25]. In addition, we found that perceived controllability was the protective factor against the emotional problems.…”
Section: Discussionsupporting
confidence: 91%
“…Besides the differences in the mean levels, these appraisals were associated with the outcomes differentially. Among the three appraisals, perceived severity was the risk factor that most widely associated with emotional and behavioural reactions, which is consistent with prior studies [22][23][24][25]. In addition, we found that perceived controllability was the protective factor against the emotional problems.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, online surveys showed a decrease in suicidal thoughts and intention during the pandemic; presentation at emergency departments due to suicidal ideation decreased , suicides in selective autopsy samples remained low 37 , and search engine users entered suicide-related terms less frequently [31][32][33]35 . However, the overall results are inhomogeneous, since other surveys indicate a high prevalence of suicidal thoughts during the pandemic, in particular under quarantine conditions 3,[38][39][40][41] .…”
Section: Discussionmentioning
confidence: 88%
“…First, psychological distress was measured by the degree of anxiety, fear and worry aroused by COVID-19 (1 = very low to 5 = very high). Such measures were used in other COVID-19 studies [20,21]. The responses were dichotomised as 'very high/high' vs. 'very low/ low/neutral'.…”
Section: Methodsmentioning
confidence: 99%